Underground cities. New frontiers in urban living. - (:unkn) unknown (Lund Humphries, 2020)
New ideas and technologies are transforming the ways we build and inhabit underground space. This book explores how these innovations can help to make our increasingly dense, climate-stressed cities both more resilient and more of a pleasure to live in. While it sets out practical design approaches, Underground Cities is not a technical manual. Designed for everyone with an interest in the future of our cities, it is beautifully illustrated and written in an accessible style that draws on the rich tradition of underworlds, both real and imagined, in art, history and poetry. Global in scope, the book ranges across continents as it surveys the vast expansion in the potential of the underground. The opening section, ‘A New Frontier’, looks at two pioneering cold-climate cities, Montreal and Helsinki, which developed new uses for the underground from the 1960s on. The closing section, ‘Looking Forward’, offers glimpses of the city of the future – of what we might be able to achieve in the next 50 or 60 years. Focusing on Hong Kong, Singapore and Tokyo, it shows projects that are going deeper, achieving a greater synergy of uses and preparing the way for new urban forms. In between, it reviews a range of innovative ideas and presents buildings and projects by leading international architects and artists, among them Jun’ya Ishigami, James Turrell, Dominique Perrault and Thomas Heatherwick, which highlight the advances in technology that are making it possible to bring the elements of nature – light, air, vegetation – deep underground. Works include a subterranean oasis, a refuge from the desert heat; a museum extension that deploys light and colour to define space; a multi-modal underground transport hub that evokes the arcades of nineteenth-century Paris, but with an added profusion of plants; and a troglodytic house and restaurant, sunk into the earth to create atmosphere.
Keywords: Untergrund; Bebauung; Resilienz; U-Bahnbau; Technische Infrastruktur; Innovation; Experimenteller Städtebau; Experimentierbau; Untergeschoss; Klimaanpassung; Stadtentwicklung; Klima